STUDI TENTANG KEAMANAN DAN KESELAMATAN PENGUNJUNG HUBUNGANNYA DENGAN CITRA DESTINASI (STUDI KASUS GEMBIRA LOKA ZOO) - Suharto, Suharto (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2016)
Image is one of the essential elements for a tourist destination and a description about the impression of a tourist destination. A good image will motivate tourist to visit a destination. The research uses Gembira Loka Zoo as an object. The purpose from this research was to identify the factors related with the image of a destination, especially in the management of the security and safety of visitors conducted by travel managers Gembira Loka Zoo. The method use in this research related to the security and safety of visitors is descriptive Research is Descriptive to investigate population and samples. Population is tourists who visit Gembira Loka Zoo and the samples are 100 respondents. In addition researchers also conduct observation, Questionnaires and documentation in the data collection. The analysis technique used there are several steps that incude the instrument of accession test, validity, reliability, hypothesis, coefficient of determination and F test and T. The result showed a Gembira Loka Zoo has a good image of tourist mind and the result showed significant correlation between Gembira Loka Zoo Image and tourist visiting motivation. With this reserach is expected that manager can improve all of the aspect of Gembira Loka Zoo so it can be motivate tourist to visit. Keywords : Gembira Loka Zoo Image, Visitor Safety and Security